PENGARUH PERIKLANAN DAN CITRA MEREK TERHADAP KEPUTUSAN PEMBELIAN SEPEDA MOTOR HONDA VARIO FI DI KOTA PEMATANGSIANTAR - DONNA VERONICA SARAGIH (JURNAL ILMIAH KOHESI, 2018)
Motorcycles as one of the automotive industry in Indonesia growth rapidly in the period of seven years after the monetary crisis in 1998. In 2005 the population of motorcycles in Indonesia has exceeded 25 million units, while the motorcycle sales data until the end of 2006 showed relatively high growth rate. Motorcycles are a prima donna for most Indonesians. The result of analysis obtained t value> from t table with regression coefficient value of 2,624> 2,009. it can be concluded that the Advertising variable (X1) partially affect the productivity (Y). Purchase decisions are affected by 48.8% by Advertising, while the remaining 51.2% are explained by other variables that are not researched. This means that Job Satisfaction has a positive influence on Purchase Decision Honda Vario FI In Pematangsiantar city. Simultaneously, the test of Job Satisfaction variable and Work Motivation on Employee Performance is done by the test f. The test result using SPSS aid obtained that the value of F equal to 33.87 with significance 0.000. F value obtained> 3.20 and supported with significance value <0.05 indicates that the two independent variables together give positive and significant influence on the dependent variable. This is supported by the test results of coefficient of determination indicating that the magnitude of the influence of two variables simultaneously is equal to 48.8% which can explain the variable productivity employee. While the remaining 51.2% is the influence of other variables that are not researched